Probing the solvation of the α-helix with extended amide III bands in Raman optical activity. Issue 5 (19th January 2022) - Yamamoto, Shigeki; Kimura, Fumiya
Abstract : Experimental and theoretical studies on the Raman optical activity (ROA) of α-helical peptides and proteins clarify that the ROA intensity ratio of the two extended amide III bands can be a permittivity indicator of the surrounding medium of the α-helix. Abstract : Experimental and theoretical Raman optical activity (ROA) study of α-helical peptides and proteins has suggested that the relative intensity of two extended amide III ROA bands at ∼1340 cm −1 (I band) and ∼1300 cm −1 (II band) can be used to monitor the permittivity of the surrounding medium of the α-helix. So far, the ROA intensity ratio, I I / I II, has been interpreted from two different viewpoints. The first one is in terms of a direct effect of permittivity around the α-helix. The second one is based on a structural equilibrium of two types of α-helical structures, "hydrated" and "unhydrated" ones. In the present study, temperature- and solvent-dependences of I I / I II are measured for highly-α-helical peptides and compared to the theoretical spectra while varying the permittivity or the type of α-helical structure. A fragment method with partial optimization in the normal modes is adopted in density functional theory calculations. The main features of the experimental spectra and a trend of the observed I I / I II are well reproduced by the simulations, which leads us to a conclusion that the I I / I II is dominantly governed by a direct influence of the permittivity of the environment and just accessorily by the equilibrium of the two types of α-helices. The simulations also opposed the conventional assignments of the I and II bands to "hydrated" and "unhydrated" α-helical structures, respectively. In the case of α-helical proteins, solvent exposure of the α-helix may be monitored by the ROA ratio.